Correlation Analysis of Ultrasound Elastography Score with Invasive Breast Cancer and Biological Prognostic Factors. (4th July 2022) - Fu, Q.; Wan, F.; Lu, Q.; Shao, W.; Fu, G.; Wang, Z.
Abstract : Invasive breast cancer (IBC) is a kind of malignant tumor in which cancer cells have broken through the basement membrane of breast ducts or lobular acini and invaded the stroma. Although ultrasound elastography score (UES) has shown unique advantages in the diagnosis of IBC, its value in the prognosis is not clear. Here, we explored the correlation of UES with IBC and biological prognostic factors. The datum of 86 patients with suspected IBC from January 2018 to December 2021 was collected. UE was applied in the examination of all patients. The lesion tissue of the malignant group was punctured to detect and analyze the expression of biological prognostic factors, including estrogen receptor (E receptor), progesterone receptor (P receptor), and human epidermal growth factor 2 (HER factor 2) and Ki67. The differences in UES under different biological prognostic factors were compared. The receiver operating characteristic (ROC) curve was applied to analyze the diagnostic value of UES of IBC and the expression of biological prognostic factors. Based on the pathological diagnosis results, the sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of UES in the diagnosis of IBC were analyzed. The correlation of UES with IBC and biological prognostic factors was analyzed by multiple linear regression and Spearman method. ROC analysis showed that the area under the curve of UES for diagnosing IBC and evaluating the expression of P receptor, HER factor 2, and Ki67 were 0.877, 0.704, 0.763, and 0.820, respectively ( P ＜0.05). The sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of UES when diagnosing IBC were 92.42%, 90.00%, 91.86%, 96.83%, and 78.26%, respectively. The UES of E receptor expression (positive and negative group) showed no obvious variance (P > 0.05). The UES of P receptors (positive and negative), HER factor 2 (positive and negative), and Ki67 (high and low expression) showed obvious differences (P < 0.05). Multiple linear regression and Spearman indicated UES was significantly correlated with the expression of P receptor, HER factor 2, and Ki67 ( P ＜0.05). UES has a certain diagnostic value for IBC and is significantly correlated to the expression of P receptor, HER factor 2, and Ki67, which is helpful for evaluating the prognosis of patients with IBC.